Factorisation

Asked by rajat951 | 22nd Sep, 2009, 09:55: PM

Expert Answer:

7x2 + 2√14x + 2 = 7x2 + 2√(7x2)x + 2 

=7x2 + 2√7√2x + 2

=(√7x)2 + 2√7√2x + (√2)2

= (√7x + √2)2 = (√7x + √2)(√7x + √2)........................Answer

40x7y2 - 135x4y5

= 5x4y2(8x3 - 27y3)

Using a3 - b3 = (a - b)(a2 + ab + b2)

= 5x4y2(2x - 3y)(4x2 + 6xy + 9y2)    ...............................Answer

Regards,

Team,

TopperLearning.

 

Answered by  | 25th Sep, 2009, 03:49: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.